2009
DOI: 10.1002/app.30239
|View full text |Cite
|
Sign up to set email alerts
|

Application of poly 3‐methylthiophene for removal of silver ion from aqueous solutions

Abstract: This article deals with application of poly (3-methyl thiophene) synthesized chemically on the surface of wood sawdust (termed as P3MTh/SD) and then was used for removal of silver ions (Ag þ ) from aqueous solution. The polymer was synthesized directly on the surface of sawdust, which has previously soaked in monomer solution using ferric chloride as chemical oxidant. The sorption experiments were performed on both batch and column systems under simple open circuit conditions. The effects of some important par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 29 publications
(55 reference statements)
0
19
0
Order By: Relevance
“…Some examples of these functional groups in chelating resins studied for the adsorption, separation or concentration of silver ions are thiourea [6,7,[18][19][20], dithiocarbamate [1,[20][21][22][23], bisthiourea [24], thiol and amine [1,3,4], thiosemicarbazide [25], polythiazaalkane [26], 2-mercaptobenzothiazole [27], thiophene [28] and amberlite XAD-16 resin [29].…”
Section: Introductionmentioning
confidence: 99%
“…Some examples of these functional groups in chelating resins studied for the adsorption, separation or concentration of silver ions are thiourea [6,7,[18][19][20], dithiocarbamate [1,[20][21][22][23], bisthiourea [24], thiol and amine [1,3,4], thiosemicarbazide [25], polythiazaalkane [26], 2-mercaptobenzothiazole [27], thiophene [28] and amberlite XAD-16 resin [29].…”
Section: Introductionmentioning
confidence: 99%
“…separation and sensors) are mostly based on their electrical conductivity and electroactivity which have been used under applied potential or current in an electrochemical cell. Moreover, we have previously reported that these polymeric materials can be used for electroless removal of some heavy metal ions from aqueous solutions with high performance [25][26][27]. This paper deals with the investigation of another possible application of polypyrrole for the removal of dyes from aqueous solutions.…”
Section: Introductionmentioning
confidence: 99%
“…All these properties confirm that polythiophene is an excellent candidate for pre -concentration and electrochemical sensing of 1-OHP. Poly(3-methylthiophene) (P3MT) is a widely used electronically polythiophene derivative, which can be easily electrodeposited onto electrode by electrooxidation of its monomer at lower potential compared to polythiophene and other derivatives [32,33]. Numerous studied have shown that P3MT modified electrodes can minimize the surface fouling and effectively electrocatalyze oxidation of some conjugated compounds, such as dopamine [34,35], 8-hydroxy-2 0 -deoxyguanosine [36,37] and phenolic compounds [38,39].…”
Section: Introductionmentioning
confidence: 99%